Valorization of grape (Vitis vinifera) leaves for bioactive compounds: novel green extraction technologies and food-pharma applications - Singh, Jyoti; Rasane, Prasad; Kaur, Rajdeep; Kaur, Harmandeep; Garg, Ritika; Kaur, Sawinder; Ercisli, Sezai; Choudhary, Ravish; Skrovankova, Sona; Mlcek, Jiri (Frontiers in Chemistry, 2023)
Grape leaves, scientifically known as Vitis vinifera, the primary by-product obtained after the processing of grapes, are gathered in enormous amounts and disposed of as agricultural waste. For more sustainable agriculture and better food systems, it is crucial to investigate these byproducts’ nutritional values. The primary bioactive compounds present in grape leaves are quercetin, resveratrol, caffeic acid, kaempferol, and gallic acid, which favour pharmacological effects on human health such as antioxidant, anti-inflammatory, anti-obesity, anti-diabetic, and hepatoprotective. Furthermore, grape leaves extract has been used as a functional ingredient for creating both food and non-food products. The aim of the current review is to review the nutritional and phytochemical composition of various varieties of grape leaves, their health-promoting characteristics and their applications. The study also highlights the various extraction techniques including conventional and non-conventional methods for extracting the various bioactive compounds present in grape leaves. Grape leaves bioactives can be extracted using environmentally safe and sustainable processes, which are in line with the rising demand for eco-friendly and healthful products worldwide. These methods are perfectly suited to the changing needs of both customers and industries since they lessen environmental effect, enhance product quality, and offer financial advantages.